Obstacles to Vocational Rehabilitation for people with InteIIectuaI Disabilitity from The Point of View of Special education Teachers in the Secondary School in Tabuk City - Alfaqir, Taghreed Atallah; Asiri, Mohammed Abdullah (Journal of Educational and Psychological Sciences, 2023)
Disabilitity from The Point of View of special education Teachers in the Secondary School in Tabuk City, and to reveal the extent to which there are statistically significant differences between the average responses of the study sample members due to the study variables:(educational level- number of years of experience- specialization- gender) to qualification obstacles professional (social, educational, psychological), and the descriptive analytical approach was used, and the questionnaire was a tool for data collection.The study consisted of three axes, namely: Obstacles of Vocational Rehabilitation programs for people with InteIIectuaI Disabilities towards (social Obstacles, educational Obstacles, and psychological Obstacles) in the city of Tabuk, with a total of (30) paragraphs, it was field applied to the study sample of (38) male and female teachers, and then they who were chosen by the intentional method.The study reached several results, the most important of which are: The response of the study sample members to the axis (social Obstacles in vocational rehabilitation programs for people with intellectual disabilities from the point of view of teachers) came to a high degree, with an arithmetic average of (4.12) and the response of the study sample to the axis (Educational obstacles in vocational rehabilitation programs for people with intellectual disabilities from the point of view of teachers) came to a high degree, with an arithmetic average of (4.06), and the response of the study sample members to the axis (psychological obstacles in vocational rehabilitation programs for people with intellectual disabilities from the teachers point of view) to a high degree, with an arithmetic mean ability(3.94), and the study found that there were no statistically significant differences at the level(0.05) between the response of the study sample members acceding to the educational level, number of years of experience, specialization, and gender in all axes. And in light of the results a number of recommendations were presented, including: communication and cooperation between special education schools and government institutions for the rehabilitation and employment of people with disabilities, preparing training courses to help students with intellectual disabilities to choose rehabilitation paths commensurate with abilities and the future aspirations of vision 2030.
Keywords: obstacles; vocational rehabilitation; intellectual disability; Tabuk City